(untitled) (Ágora Journal, 2024)
In Empire Brazil, the dynamics of urban life were sustained by the work of blacks forced into slavery. Their activities ranged from transporting people and cargo to maintaining a busy street trade, driving the wheels of the city’s economy. Because of the specific nature of their work on the streets, they did not have the typical plantation foreman - so they enjoyed a freedom of movement that captives in rural areas never had. However, this does not mean that they lived without any kind of restriction since, in the cities, the overseers were replaced by surveillance apparatuses linked to the state. This article examines the specific features of slave labor and the efficiency of the police in controlling the enslaved in the 19th century (1830-1850), based on manuscript and printed documents and a bibliography pertinent to the subject.